Celdas solares que contienen tintes sensibilazantes para la producción de energía. - Meza-Benavides, Carlos; Pineda, Leslie; Coto-Cortés, Aníbal; Morales-Hernández, Sergio; Pérez-Rodríguez, Javier; Vega-Castillo, Paola (Instituto Tecnológico de Costa Rica, 2013)
This project is about the work done by a group of engineers of the Costa Rica Institute of Technology (ITCR) over a new solar cell type developed by a work group of the Costa Rica University (UCR). The novelty of the cells is the use of sensitizing tints in order to absorb light and take it to a semiconductor material that perform the generation of electric energy from solar energy. The work group of the ITCR implemented the instrumentation and measurement techniques of the current vs. voltage (i – v) of the solar cells with sensitizing tints synthesized by the UCR group. The main result of this work is the i – v curve that characterizes the developed cell.
Proyecto de Investigación (Código: VIE-5402-1360-2301) Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ingeniería Electrónica, 2013
Keywords: Fuentes de energía; Minerales; Instrumentación; Caracterización; Energía